(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
In this paper, we calculate the variables for regular concrete that have been observed but not put on a mathematical basis. Concrete is widely used and is a n important building material. Understanding concrete better is important considering that a lot of infrastructure repair work in the US will be done in the short term- work that has been neglected for far too many years. Concrete repair is a large part of that work.